GIVEN:
y = [ 2/(3x²) ] - [ 4/(5x) ]
FIND:
The value(s) of "x".
LET:
y = 0 , to determine the root(s) of the function.
Let's start by SUBSTITUTING, using (PARENTHESIS), the value of "0" for "y".
___________________________
SOLUTION:
y = [ 2/(3x²) ] - [ 4/(5x) ]
(0) = [ 2/(3x²) ] - [ 4/(5x) ]
1(0) = [ 2/(3x²) ] - [ 4/(5x) ]
0 = [ 2/(3x²) ] - [ 4/(5x) ]
Now, SIMPLIFY the Right Hand Side of the equation by combining "like" terms.
First, we need a Greatest Common Factor to subtract the two fractions.
________________________________________
(0) = [ 2/(3x²) ] - [ 4/(5x) ]
GCF= 15x²
Multiply numerator and denominator by the SAME factor to get a denominator = 15x².
_____________________________________________
0 = { [(2)(5)] / [(3x²)(5)] } - { [(4)(3x)] / [(5x)(3x)] }
0 = [10/(15x²)] - [(12x)/(15x²)]
COMBINE "like" terms.
___________________________________
0 = [(10 - 12x)/(15x²)]
Factor out the GCF in the Numerator.
___________________________________________
0 = { [2(5 - 6x)] / (15x²) }
0 = [2/(15x²)] [(5 - 6x)/(15x²)]
Set each factor = 0, and SOLVE for "x" in the numerator.
______________________________________________
REMEMBER:
The denominator ≠0
Therefore, 15x² ≠0.
15x² ≠0
(15x²)/15 ≠0/15
x² ≠0
x² ≠0
√(x²) ≠±√(0)
x ≠±(0)
x ≠±1(0)
x ≠0
_____________________________
RESTRICTION on "x":
x ≠0
___________________________
Setting the numerator(s) = 0 and SOLVING for "x", we get:
[2/(15x²)] = 0 ; x ≠0
2 = 0
2 ≠0 Therefore, there is no x-intercept for this factor.
[(5 - 6x)/(15x²)] = 0 ; x ≠0
5 - 6x = 0
5 - 5 - 6x = 0 - 5
0 - 6x = -5
-6x = -5
-6x/(-6) = [ (- 5) ÷ (-1) ] / [ (-6) ÷ (-1) ]
x = [ (- 5) ÷ (-1) ] / [ (-6) ÷ (-1) ]
REDUCE for final answer! :o)
________________________________
FINAL ANSWER:
x = 5/6, where x ≠0
DOMAIN: all REAL numbers excluding zero. (- ∞, 0) U (0, ∞)
Good question! Contrats. on making to the end! ♥
2006-12-03 05:52:30
·
answer #1
·
answered by LovesMath 3
·
0⤊
0⤋
x = 0.833333[...]x^2-1.25y
"x" equals eight and one-third tenths times x squared minus one and 1-quarter y.
X^2 and X aren't divisible in the same sequence. You need to isolate the variable the problem was already simplified as far is it could go when you gave it to us.
Ironduke, she said only one of the "X"s is squared.
Vivek would be right because its given in simplest form and there is no way to isolate the x and find y. without finding out y you can't find x. its already simplified.
2006-12-03 04:41:21
·
answer #2
·
answered by I 4
·
0⤊
0⤋
ok the only way is to simplify which is x(2/3x-4/5) thats the only thing i can think of
2006-12-03 04:19:44
·
answer #3
·
answered by Anonymous
·
0⤊
1⤋
y= 2/(3x^2) -4/(5x)=0
10/(15x^2) -12x/(15x^2) =0
(10-12x)/(15x^2)=0
10-12x = 0
-12x=-10
x = 5/6
2006-12-03 04:31:51
·
answer #4
·
answered by ironduke8159 7
·
1⤊
0⤋
the answer or its simpliest form is:
y= 2(5x-6)/15
how did i get it:
y= 2/3x (x^2/1) -4/5x
=2x^2/3x -4/5x
=10x^2 - 12x/ 15x ---> lcd
=2x(5x-6) / 15x ------> common monomial factor
y=2(5x-6) / 15
2006-12-03 04:16:06
·
answer #5
·
answered by dainty 1
·
0⤊
3⤋
y= -2/15x squared
thats all i got.... its hard
2006-12-03 04:18:22
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋
You didn't specify what you're looking for.
2006-12-03 04:16:37
·
answer #7
·
answered by Jim Burnell 6
·
0⤊
2⤋
wat do u actually want out of tis equation .
ya i got that y=2/3 x^2 - 4/5 x
but wat is to be done . wats the question
2006-12-03 04:17:29
·
answer #8
·
answered by Anonymous
·
1⤊
0⤋